INTEGRATION OF DEEP LEARNING TECHNOLOGY IN ISLAMIC RELIGIOUS EDUCATION (PAI) - Yahriyah, Siti; Rakhmawati, Rakhmawati; Nasikin, Moh.; Hadi, Anas; Setyaningrum, Titis; Ventura, Ragusfi Bhuena (Jurnal Konseling Pendidikan Islam, 2025)
This study examines how deep learning is incorporated into the Independent Curriculum for Islamic Religious Education (PAI). Using a qualitative approach based on literature study, this study finds opportunities, problems, and new models to support students' deep understanding and strengthening of Islamic character. Through technology-based approaches such as digital platforms, interactive applications, and project-based learning, deep learning has great potential to improve students' understanding of Islam. Students can not only understand Islamic concepts academically but also apply them in their daily lives with the help of this technology. However, several obstacles hinder the implementation of deep learning, such as limited technological infrastructure, teacher and student readiness, and the challenge of balancing the use of modern technology with the preservation of Islamic values. Therefore, this study proposes a model that combines Islamic values ​​with modern technology, such as AI and adaptive learning systems. This model aims to improve the cognitive, affective, and psychomotor aspects of the overall learning experience. In addition, this study suggests ways to improve teachers' abilities through special training, strengthen government policies on the digitalization of education, and encourage the development of technology based on Islamic principles. The results of this study are expected to encourage the implementation of in-depth learning in the Independent Curriculum, improve Islamic Religious Education learning, and instill Islamic character in students that are in accordance with the needs of the digital age. Therefore, technology integration can help in-depth learning while maintaining the core of Islamic teachings.